THE EFFECTIVENESS OF PEER TUTOR LEARNING MODEL ON MATHEMATICS LEARNING OUTCOMES ON SOCIAL ARITHMETIC MATERIAL: (Efektifitas Model Pembelajaran Tutor Sebaya Terhadap Hasil Belajar Matematika Pada Materi Aritmatika) - Hentihu, Vivi (Uniqbu Journal of Exact Sciences, 2021)
Mathematics is one of the subjects in schools that gets the most significant attention from educators, parents, and children. The problem in this research is how the Effectiveness of Peer Tutor Learning Model on Mathematics Learning Outcomes in the Social Arithmetic Material of Class VII Students of SMP Negeri 40 Buru ". This research method is pre-experimental with a one-group pretest-posttest design to know the peer tutor learning model’s effectiveness in learning mathematics on social arithmetic material. The population in this study was all class VII students. SMP Negeri 40 Buru for the 2019/2020 school year, totaling 34 students and two classes, namely class VII1 and VII2. This study sample was one class from the entire population selected using the quota sampling technique, namely class VII1. The results showed that based on the results of the student activity analysis, it was found that the average score of the observed student activity was 3.47, the average was in an outstanding category. This shows that learning using the peer tutor learning model can activate students in education. This is marked by a decrease in the number of students who are less active in group work and doing other activities outside of learning activities. Most students have great interest and enthusiasm in learning mathematics on social arithmetic material using the peer tutor learning model. Based on the student response questionnaire results as a whole, learning mathematics using the peer tutor learning model gets a positive response with the acquisition of an average percentage of student responses that is 80.5%. Using the peer tutor learning model in learning mathematics in the classroom provides opportunities for students to exchange ideas with friends or teachers in solving problems so that this condition creates a positive response from students in learning.